Assessment of small to medium enterprises’ (SMEs) role towards livelihoods of marginalized Harare women: case of Harare city center - Chimbaira, Marilyn (Midlands State University, 2017)
This study sought to evaluate the extent to which the SMEs sector has contributed towards the livelihood options of marginalized women in Harare. This group was chosen firstly because women world over have the greatest burden of taking care of the family but are sidelined in the development process as they have limited access to opportunities compared to men preventing them from fending for their families. Focus was put on Harare because past research seems to be mostly biased towards rural women at the expense of urban women. Harare being the capital would represent activities carried out by women in other provinces too. The study focused on an area within town because most women within the sector operate in town. Results indicated women within the sector have become empowered through their participation and their lives have changed for the better showing strategies within the sector seem to have a great significance in their lives. However, women remain limited in certain jobs like Information Technology and Repairs amongst others which also seem to bring better remuneration compared to the areas that the majority of women are involved in.